Risk of pancreatic cancer in Minia district, Egypt - Abdelrehim, Marwa G.; Mahfouz, Eman M.; Ewis, Ashraf A.; Seedhom, Amany E.; Afifi, Hassan M.; Shebl, Fatma M. (International Journal Of Community Medicine And Public Health, 2017)
Background: Pancreatic cancer is considered one of the most lethal malignant neoplasms. Therefore, a better understanding of the etiology and identifying the risk factors are essential for the development of preventive strategies. Methods: This case-control study included pancreatic cancer patients attending Minia Cancer Center during the period from June 2014 to December 2015 and controls from the general population. Several suspected risk factors were evaluated during personal interviews with the study participants. Statistical analysis included crude odds ratio (OR) and multivariable logistic regression with an adjusted OR and 95% confidence interval (CI). Results: The study included 224 subjects, 75 pancreatic cancer cases, and 149 controls. Cases had higher age and male gender than controls. Bivariate analyses showed that age, sex, smoking, family history of pancreatic cancer, physical activity, mental stress, age at first birth, hormonal contraception, diabetes, hepatitis C virus (HCV) infection, pancreatitis, and cholecystitis were associated with pancreatic cancer. In the final multivariable analysis, smoking, physical activity, diabetes, HCV infection, and cholecystitis were significantly associated with pancreatic cancer risk. Conclusions: Pancreatic cancer risk is associated with some potentially modifiable factors like tobacco smoking and low physical activity and related health problems as diabetes, HCV infection, and cholecystitis. Control of known risk factors for pancreatic cancer should be considered to help in risk reduction and prevention.